Female community-based agents: Archetypes and experience with farmers - Kaur, Jasleen (60 Decibels, 2023)
Alliance for a Green Revolution (AGRA) has developed a Village Based Advisor (VBA) model to bring timely advice, access to inputs, technology and markets closer to smallholders in African countries. Through this model, AGRA identifies and trains lead farmers to be VBAs and support other farmers in the area. 60 Decibels conducted a study to help AGRA explore VBA archetypes and experience with farmers in Burkina Faso and Nigeria. We are also currently undertaking the last of the three studies to understand VBAs’ journeys. The objective of the research is to help AGRA understand how to better support female VBAs and the female farmers they serve in order to catalyze agricultural transformation and food security. This presentation would therein convene a panel from AGRA, Tanager, and 60 Decibels to discuss: findings of the research related to: profile and motivation of VBAs, preparedness for this work, scale and type of services provided to farmers, and their effectiveness and impact as perceived by farmers; actionable recommendations and insights from the data collected across over 1,000 VBAs and 500+ farmers; and how further supporting VBAs through greater understanding of barriers, needs, and motivations, and capacity strengthening can help them play an important role among farmers— particularly female farmers.